Social Issues Surrounding the Adolescent with Asperger Syndrome: Perceptions of Parents and Teachers - Hurlbutt, Karen; LaPlante, Elaine (Journal of the American Academy of Special Education Professionals, 2010)
The purpose of this qualitative study, a focused case study of a community, was to investigate the perceptions and experiences of three parents and three teachers regarding social issues of adolescents with Asperger Syndrome (AS). The study revealed that, in this small, rural community, students with AS are supported by their peers, appear to be content with who they are, and the parents and teachers foster a positive social climate that promotes acceptance and understanding.